A home‐based progressive resistance exercise programme for patients with venous leg ulcers: a feasibility study. Issue 4 (14th June 2012) - O'Brien, Jane; Edwards, Helen; Stewart, Ian; Gibbs, Harry
Abstract : This study aimed to assess the feasibility of a home‐based exercise programme and examine the effects on the healing rates of venous leg ulcers. A 12‐week randomised controlled trial was conducted investigating the effects of an exercise intervention compared to a usual care group. Participants in both groups ( n = 13) had active venous ulceration and were treated in a metropolitan hospital outpatients clinic in Australia. Data were collected on recruitment from medical records, clinical assessment and questionnaires. Follow‐up data on progress in healing and treatments were collected fortnightly for 12 weeks. Calf muscle pump function data were collected at baseline and 12 weeks from recruitment. Range of ankle motion data were collected at baseline, 6 and 12 weeks from recruitment. This pilot study indicated that the intervention was feasible. Clinical significance was observed in the intervention group with a 32% greater decrease in ulcer size ( P = 0·34) than the usual care group, and a 10% ( P = 0·74) improvement in the number of participants healed in the intervention group compared to the usual care group. Significant differences between groups over time were observed in calf muscle pump function parameters [ejection fraction ( P = 0·05), residual volume fraction ( P = 0·04)] and range of ankle motion ( P = 0·01). This pilot study is one of the first to examine and measure clinical healing rates for participants involved in a home‐based progressive resistance exercise programme. Further research is warranted with a larger multi‐site study.